Design Variations on Planar Differential Antenna with Potential for Multiple, Wide, and Narrow Band Coverage - Domenico Pepe; Luigi Vallozzi; Hendrik Rogier; Domenico Zito (International Journal of Antennas and Propagation)
This paper presents three practical antenna implementations based on variations of one general planar differential antenna topology originally proposed for ultrawideband (UWB) applications. All designs were implemented on a low-cost FR4 substrate and experimentally characterized in an anechoic chamber. The results show how the proposed design variations lead to the required antenna performances and how they give rise to new opportunities in terms of coverage of wide, narrow, and multiple frequency bands for communication and sensing applications below 5 GHz. In particular, the results show how a significant enhancement in bandwidth performance is achieved by folding the differential radiating elements. Moreover, they show how an agile design strategy enables adaption of the antenna design to different requirements for covering wide, narrow, and multiple bands, making the proposed class of antennas suitable for different wireless applications. In detail, the proposed class of antennas covers multiple frequency bands, ranging from the 868 MHz and 915 MHz bands to 2.4 GHz industrial scientific and medical (ISM) bands, including the 1.2 GHz L band for Global Positioning and Navigation Satellite Systems (GNSS) and the lower portion of the UWB band.